Serum IgG Antibodies from Pregnant Women Reacting to Mimotopes of Simian Virus 40 Large T Antigen, the Viral Oncoprotein - Mazzoni, Elisa; Di Stefano, Mariantonietta; Fiore, Josè R.; Destro, Federica; Manfrini, Marco; Rotondo, John Charles; Casali, Maria V.; Vesce, Fortunato; Greco, Pantaleo; Scutiero, Gennaro; Martini, Fernanda; Tognon, Mauro G. (Frontiers in Immunology, 2017)
Simian virus 40 (SV40) large T antigen (LT) coding sequences were revealed in different human samples, whereas SV40 antibodies (Ab) were detected in human sera of cancer patients and healthy individuals, although with a lower prevalence. Previous studies carried out by the neutralization assay gave a SV40 seroprevalence, in the general population, up to 8%, although higher rates, 12%, were detected in kidney transplant children, in a group of HIV-positive patients, and in healthy females. In this study, serum samples from pregnant women, together with those from non-pregnant women, were analyzed to check the prevalence of IgG Ab reacting to SV40 LT antigens. Serum samples were collected from pregnant and non-pregnant women, with the same mean age. Women were in the range of 15–48 years old. Samples were assayed by an indirect ELISA employing specific SV40 LT mimotopes as antigens, whereas functional analysis was performed by neutralization of the viral infectivity in cell cultures. As a control, sera were analyzed for Ab against BK polyomavirus (BKPyV), which is a human polyomavirus homologous to SV40. Statistical analyses employed chi-square with Yates’ correction, and Student’s t tests. Indirect ELISAs indicated that pregnant women tested SV40 LT-positive with a prevalence of 17% (23/134), whereas non-pregnant women had a prevalence of 20% (36/180) (P > 0.05). Ab against BKPyV were detected with a prevalence of 80% in pregnant women and with a prevalence of 78% in non-pregnant women. These data indicate that SV40 infects at a low prevalence pregnant women. We may speculate that SV40, or a close human polyomavirus still undetected, could be transmitted from mother to fetus.